Students’ mental models of solid elasticity: Mixed method study - Batlolona, John Rafafy; Dıantoro, Markus; Wartono; Leasa, Marleny (Journal of Turkish Science Education, 2020)
A mental model (MM) is an internal representation of students’ conceptual understanding. Currently, students have still had difficulties in explaining the physical state of elasticity of solid materials, at sub-microscopic level. These difficulties call for this research. Through a mixed method, the study aimed to reveal the development and differences of students’ mental models after physics learning with problem -based learning (PBL) and conventional methods. Indicators of students’ mental models were adapted from SMD model. Findings suggested that the PBL resulted in more MM, whilst conventional classes emerged MM on the elastic and plastic objects. Meanwhile, the lowest MM achievements ware Hooke’s Law for the PBL, and series and parallel springs for the conventional class. N-Gain values of the students’ mental models at PBL and conventional classes were found to be 0.64 and 0.43 respectively. On the other hand, mental model scores of the PBL learning model was higher (23.77%) than those of the conventional learning model. Thus, it can be concluded that the PBL learning model is effective in improving the students’ mental models of physics. This research recommends that students’ understanding of physics concepts should be increased at macroscopic and sub-microscopic levels.